Pelaksanaan Pembiayaan Renovasi Rumah Melalui Akad Al-Murabahah Dan Wakalah Di Bank Sumut Syariah Kc. Medan - Della Septina; Rahmad Hidayat (Al-Sharf: Jurnal Ekonomi Islam, 2022)
The results of the research that can be taken from this research are, in financing the house renovation at Bank Sumut Syariah Medan Branch Office, the multi-contract used is the murabahah bil wakalah contract, when viewed from the sharia basis there is no argument that prohibits combining murabahah and wakalah contracts. , then the law is allowed, but the implementation of this multi-contract is not in accordance with the DSN-MUI Fatwa and Fiqh Muamalah, because the implementation of murabahah and wakalah contracts is carried out together in practice, before the goods are legally owned by the bank. the customer needs in accordance with the Budget Plan (RAB) for house renovation after the disbursement is complete, so that there is gharar in the object of the contract, because it is not known whether the goods purchased by the customer are in accordance with what was agreed upon because of the absence of reporting, so that the implementation of the wakalah contract on Home Renovation Financing at Bank Sumut Syariah, it is necessary to consider go back.